THE NONVERBAL COMMUNICATION: AN EXPRESSION OF THE INTERPERSONAL RELATIONSHIPS - Ivanova, Lyubov (Revista Inclusiones, 2021)
The non-verbal communication is that communication, a part of the information transmitted among people, which cannot be expressed in words. It is transmitted to a non-verbal level. The non-verbal communication represents the vast area of emotional states and expressions. The characteristic of non-verbal signs is that they are largely unaware at the time of their transmission and acceptance. They do not become a fact of consciousness, but they influence the way in which the verbal message that is being transmitted in full, is currently being passed. The non-verbal communication is a prerequisite for creating one or other attitude towards the message and to its` sender.